2021
DOI: 10.1111/pere.12389
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of romantic partners' responses to disclosures of suicidality

Abstract: This mixed‐methods study examines how adults in the United States perceive their romantic partner's response to disclosures of suicidality and how romantic relationship characteristics relate to perceptions of disclosure responses. Participants (N = 30) recruited from Reddit completed a survey using open‐ and closed‐ended questions about disclosing suicidality to a romantic partner. Qualitative findings highlight validating and invalidating disclosure responses. Validating responses include two subthemes: (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Additionally, social support is a critical protective factor preventing suicidal thoughts and behaviors. Compounding the effects of IPP, women’s relational problems with other family and friends might increase isolation, cutting off the possibility of seeking help from loved ones (Love et al, 2021; Wolford-Clevenger et al, 2019). This finding suggests that intervention efforts aimed at increasing women’s economic efficacy and social networks, which alleviate women’s financial problems and social isolation, may in turn be a form of suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, social support is a critical protective factor preventing suicidal thoughts and behaviors. Compounding the effects of IPP, women’s relational problems with other family and friends might increase isolation, cutting off the possibility of seeking help from loved ones (Love et al, 2021; Wolford-Clevenger et al, 2019). This finding suggests that intervention efforts aimed at increasing women’s economic efficacy and social networks, which alleviate women’s financial problems and social isolation, may in turn be a form of suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, women struggling with IPP mostly tend to share their suicidal ideations with their partners. While this study was not designed to determine how intimate partners responded to such disclosures among these suicide victims, studies have found that invalidating responses toward suicide disclosure, including dismissing the suicidal partner’s emotional experiences, downplaying the severity of their suicidality, or devaluing of the suicidal partner or the relationship, lead to worse outcomes (Love et al, 2021). These types of partner responses have the potential to intensify suicidal partners’ feelings of thwarted belongingness and perceived burdensomeness (Van Orden et al, 2010), increasing the risk of suicide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, disclosing to one's romantic partner will generate social support and help (e.g., calling emergency services if necessary; Frey et al, 2018;Frey et al, 2016b). Validating responses from a romantic partner most commonly include listening and expressing care and concern (Love et al, 2021). Unfortunately, many individuals experience negative reactions following the disclosure of suicidal thoughts and behaviors, even from romantic partners (Frey et al, 2016a).…”
Section: Disclosure Of Suicidal Thoughts and Behaviorsmentioning
confidence: 99%
“…Unfortunately, many individuals experience negative reactions following the disclosure of suicidal thoughts and behaviors, even from romantic partners (Frey et al, 2016a). Among individuals who disclosed suicidal thoughts or behaviors to a romantic partner, 41% reported stigmatizing reactions, such as being judged (Frey et al, 2016a) and 20% reported an increase in suicidal thoughts and behaviors after disclosing (Love et al, 2021). Among a sample of veterans who had attempted suicide, the reported least helpful disclosure of their suicide attempt was most frequently with a romantic partner (Ammerman et al, 2020).…”
Section: Disclosure Of Suicidal Thoughts and Behaviorsmentioning
confidence: 99%